((a-1)/(a+1)+(4a)/(a^2-1)) * (1/(a+1)) упростите выражение,

((a-1)/(a+1)+(4a)/(a^2-1)) * (1/(a+1)) упростите выражение,

  • (frac{a-1}{a+1}+frac{4a}{a^2-1})cdotfrac{1}{a+1}=frac{(a-1)^2+4a}{a^2-1}cdotfrac{1}{a+1}=frac{a^2-2a+1+4a}{a^2-1}cdotfrac{1}{a+1}==frac{(a+1)^2}{(a^2-1)(a+1)}=frac{1}{a-1}

  • (frac{a-1}{a+1}+frac{4a}{a^{2}-1})*frac{1}{a+1} == (frac{a-1}{a+1}+frac{4a}{(a-1)(a+1)})*frac{1}{a+1}==frac{(a-1)^{2}+4a}{(a-1)(a+1)}*frac{1}{a+1}==frac{a^{2}+2a+1}{(a-1)(a+1)}*frac{1}{a+1}==frac{(a+1)^{2}}{(a-1)(a+1)}*frac{1}{a+1}==frac{(a+1)^{2}}{(a-1)(a+1)^{2}}= frac{1}{a-1}